If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 12w + -47 Reorder the terms: 0 = -47 + 12w Solving 0 = -47 + 12w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12w' to each side of the equation. 0 + -12w = -47 + 12w + -12w Remove the zero: -12w = -47 + 12w + -12w Combine like terms: 12w + -12w = 0 -12w = -47 + 0 -12w = -47 Divide each side by '-12'. w = 3.916666667 Simplifying w = 3.916666667
| (6x-4)-(2x+8)= | | 20=12+2x | | f(-2)=4x^2-8x+3 | | -x+3x=10 | | 40x+8x=720 | | 3x-9x^2=10 | | h(x)=1/x | | Xsquared=4000 | | 20u^2-88u+32=0 | | 1=2x+4d-d+7i | | x^3-4x=21 | | log[4](36)+log[4](2x+3)=log[4](8x-14) | | 2log[4](6)+log[4](2x+3)=log[4](8x-14) | | (2x+1)(2x+3)=99 | | 0=2u-20 | | 5x/6=11/4=17/3 | | 6x^2-12x-x=0 | | 6=3n/5 | | 9=3(v+2) | | (6-i)-(9+7i)= | | 34=2w+10 | | f(15)=2.479g | | f(10)=2.479g | | 10=2(m+2) | | 3-2-210=n | | 3-2-n=210 | | 11y^2-52y+46=0 | | 3(v+1)=9 | | 3-2-210=210 | | (8/4v-24)-1=2/v-6 | | (8/4v-24)-1=(2/v-6) | | 2(v+1)=8 |